Psychological characteristics and skills of top-level Dutch gymnasts in the initiation, development and mastery stages of the athletic career - Blijlevens, S. J. E.; Elferink-Gemser, M. T.; Wylleman, P.; Bool, K.; Visscher, C. (Psychology of Sport and Exercise, 2018)
There is still only limited research available on whether the psychological characteristics and skills which facilitate successful progress throughout various stages of talent development, are the same as those contributing to elite performance. The purpose of the current study is therefore to identify the psychological characteristics and skills required by talented athletes as they develop through the initiation, development and mastery stages of an athletic career. Data was gathered from in-depth interviews with 16 top-level female gymnasts, between 10 and 24 years of age. Thematic analysis was used to interpret the data. Gymnasts emphasised that the number of different psychological characteristics and skills required increases with progression through the stages. In the initiation stage, gymnasts talk in particular about `maximising their potential`, in the development stage `working with their environment` is added, and in the mastery stage, gymnasts also talk about `delivering high performance`. The results provide useful insights for giving appropriate support in the development of psychological characteristics and skills in different stages of the athletic career.